Pumping and hygiene practices are associated with bacterial load and microbial composition in human milk expressed at home - Sarah M. Reyes; Dainelle L. Allen; Janet E. Williams; Mark A. McGuire; Michelle K. McGuire; Kathleen M. Rasmussen; Anthony G. Hay (Journal of Translational Medicine)
Abstract Background Human milk (HM) harbors a unique microbiome that contributes to the development of the infant gastrointestinal microbiome and influences long-term health outcomes. While pumping and bottle-feeding HM are increasingly common, doing so may introduce exogenous bacteria, altering this microbial community. The extent to which real-world pumping and hygiene practices alter the HM microbial community remains inadequately characterized. Methods We conducted a secondary analysis of 104 paired milk samples from 52 healthy women to investigate the associations between at-home pump hygiene practices and the HM microbiota. We compared samples expressed with personal equipment, allowing women to follow their typical practices, noting variations in breast pump types (closed- vs. open-systems), pre-pumping handwashing, and collection kit cleaning practices (OWN). Milk was also expressed with hospital-grade pump with new, commercially sterilized equipment kits under study-controlled conditions (STER) to serve as a control representing each woman’s own unaltered milk microbiota. Microbiota composition was characterized using aerobic culture and 16S rRNA gene sequencing. Results Among OWN milk samples, personal breast pump type had little impact on the HM microbiota. Pre-pumping handwashing, practiced by only 22% of participants, was associated with lower bacterial counts. Compared to samples expressed with handwashed kits, those expressed using home-sterilized kits yielded fewer total and gram-negative bacterial counts, and lower relative abundances of Proteobacteria. The microbiota of OWN milk samples expressed with home-sterilized kits more closely resembled STER samples even in the absence of pre-pumping handwashing (R 2 = 0.36; P < 0.001). Conclusions At-home hygiene practices, particularly collection kit cleaning methods, substantially influence the HM microbiota. Home sterilization of collection kits may minimize changes to the HM microbiota during expression. These findings support evidence-based recommendations for hygienic pumping practices and underscore the need for further research on the health implications (if any) of pumping-dependent variations in the HM microbiota on infant health.